2000
DOI: 10.1097/00006534-200004050-00014
|View full text |Cite
|
Sign up to set email alerts
|

Palatal Distraction in a Canine Cleft Palate Model

Abstract: The purpose of this study was to determine whether the canine hard palate can be lengthened by distraction osteogenesis in a cleft palate model using a mostly submucosal distractor. Five mongrel dogs were used. After raising mucoperiosteal flaps, a midline strip of bone was removed from the hard palate of each dog to simulate the bony defect seen in a cleft palate. A transverse osteotomy was then made to separate the posterior segment of the hard palate from the anterior segment. Posterior osteotomies were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The cats used in this study were all juveniles aged 0.5-0.8 years old; the longest time interval followed after active distraction was 12 weeks, after which the cats would have reached maturity. It could therefore be observed that there was no influence of the DO technique on development of the oral and maxillofacial area 3,4 . In addition, comparative measurement of the jaws using experimental casts implied that the DO procedure might not retard the normal developmental tendency of the midface, and could maintain a normal occlusal relation in these cats.…”
Section: Discussionmentioning
confidence: 94%
“…The cats used in this study were all juveniles aged 0.5-0.8 years old; the longest time interval followed after active distraction was 12 weeks, after which the cats would have reached maturity. It could therefore be observed that there was no influence of the DO technique on development of the oral and maxillofacial area 3,4 . In addition, comparative measurement of the jaws using experimental casts implied that the DO procedure might not retard the normal developmental tendency of the midface, and could maintain a normal occlusal relation in these cats.…”
Section: Discussionmentioning
confidence: 94%
“…Ascherman et al 18 also studied hard palate lengthening with DO in a canine model. They used a 10-day la-tency period, and distracted at a rate of 0.675 mm/d for 15 consecutive days, with 8 weeks of consolidation.…”
Section: Resultsmentioning
confidence: 99%
“…All 5 dogs they studied had new bone formation at the site of distraction. Ascherman et al 18 concluded that it is possible to lengthen the canine hard palate with DO.…”
Section: Resultsmentioning
confidence: 99%
“…Problems associated with maxillary retrusion are functional and esthetic as facial disfigurement, occlusal problems, temporomandibular joint pain, and psychological problems [8], [9]. The maxilla should be advanced to a position that catches up to the mandibular growth.…”
Section: Introductionmentioning
confidence: 99%